(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Identify some characteristics of small liver fluke infections in the Lia communes of Quang Tri Province and to identify the small liver fluke species Clonorchis sinensis using morphological and molecular methods. Research method: A cross-sectional descriptive study was conducted on 402 individuals aged 2 years and older in Lia and A Doi communes of Quang Tri Province, using the Kato-Katz stool examination method and the stool washing technique for recovering adult flukes. Results: The prevalence of small liver fluke infection was 29,60%, including 32,00% in A Doi commune and 27,23% in Lia commune. Several small liver fluke specimens were collected and identified based on morphological characteristics and molecular biology, confirming the first detection of the small liver fluke Clonorchis sinensis in Lia commune, Quang Tri province. Conclusion: The prevalence of small fluke infection was determined in the community of the Lia area, Quang Tri province, with the highest infection rate found in the working-age group over 20 years old. The study also confirmed the first presence of the small liver fluke Clonorchis sinensis in in Quang Tri province.